The influence of the stratosphere on the tropospheric zonal wind response to CO2 doubling - C. J. Bell; P. C. Siegmund; Y. B. L. Hinssen (Atmospheric Chemistry and Physics, 2011)
The influence of a CO2 doubling on the stratospheric potential vorticity (PV) is examined in two climate models. Subsequently, the influence of changes in the stratosphere on the tropospheric zonal wind response is investigated, by inverting the stratospheric PV. Radiative effects seem to dominate the stratospheric response to CO2 doubling in the Southern Hemisphere. These lead to a stratospheric PV increase at the edge of the polar vortex, resulting in an increased westerly influence of the stratosphere on the troposphere, increasing the midlatitude tropospheric westerlies in late winter. In the Northern Hemisphere, dynamical effects are also important. Both models show a reduced polar PV and an enhanced midlatitude PV in the Northern Hemisphere winter stratosphere. These PV changes are likely related to an enhanced wave forcing of the winter stratosphere, as measured by an increase in the 100 hPa eddy heat flux, and result in a reduced westerly influence of the stratosphere on the high latitude tropospheric winds. In one model, the high latitude PV decreases are, however, restricted to higher altitudes, and the tropospheric response due to the stratospheric changes is dominated by an increased westerly influence in the midlatitudes, related to the increase in midlatitude PV in the lower stratosphere. The tropospheric response in zonal wind due to the stratospheric PV changes is of the order of 0.5 to 1 m s−1. The total tropospheric response has a somewhat different spatial structure, but is of similar magnitude. This indicates that the stratospheric influence is of importance in modifying the tropospheric zonal wind response to CO2 doubling.